Welding method for composite current collector pole piece of laminated battery
By welding the adapter foil in the white space of the composite liquid collector pole sheet, combined with ultrasonic welding and press-fusion welding technology, the problem of waste and welding difficulty of metal foil in the existing composite liquid collector pole sheet welding process is solved. , achieving high-quality welding effect.
Patent Information
- Application Number
- CN202411698658.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-26
AI Technical Summary
In the existing composite fluid collector sheet welding process, the need for doubled copper/aluminum foil leads to increased difficulty in welding process and waste of metal materials.
The adapter foil is welded in the white space of the composite liquid collector pole sheet, and the use of metal foil is reduced while improving welding quality.
It effectively reduces the waste of metal foil, reduces the difficulty and burden of welding process, and improves the welding quality and reliability of welding parts.
Smart Images

Figure CN119447320A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pole piece welding, in particular to a method for welding a composite current collector pole piece of a laminated battery. Background Art
[0002] Composite current collectors have attracted widespread attention in the lithium battery industry because they can improve the energy density and safety of batteries and reduce costs to a certain extent. The composite current collectors under existing technologies mainly deposit copper / aluminum metal layers on the surface of PET / PP substrates. The metal layers on both sides are not in direct contact with each other, but only combined with the polymer base film to form a "sandwich structure". Therefore, when it is applied to lithium-ion batteries, it needs to be processed by transfer welding. By leading out a layer of conventional metal foil on each of the metal layers on both sides, the metal layers on both sides can be conductive, thereby ensuring normal battery performance.
[0003] The existing composite current collector welding solution mainly involves transferring and welding a layer of traditional foil (usually copper / aluminum foil) on both sides of the pole piece. Compared with traditional pole pieces, the number of foil layers required to be welded in the composite current collector pre-welding process is often doubled, which undoubtedly increases the difficulty of the welding process and increases the loss of copper / aluminum foil to a certain extent.
[0004] Based on this, the present invention will provide a composite current collector electrode welding method for a laminated battery, which can reduce the waste of metal foil in the current composite current collector transfer welding process and reduce the burden of subsequent pre-welding processes. Summary of the invention
[0005] The object of the present invention is to provide a composite current collector electrode welding method for a laminated battery to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions: A composite current collector electrode welding method for a laminated battery, specifically comprising: (1) coating the electrode paste on both surfaces of a plurality of composite current collectors, leaving a blank area for the electrode tabs, and drying to obtain composite current collector electrode sheets; (2) Welding the transfer foil in the blank area of the tab of the composite current collector electrode to be laminated; (3) stacking the composite current collector pole pieces welded in (2) in sequence. After the stacking is completed, welding the upper and lower stacked composite current collector pole pieces so that the transfer foil is in full contact with the tab blank areas of the upper and lower composite current collector pole pieces, thereby obtaining a semi-finished laminated current collector pole piece; (4) The welding parts of the semi-finished laminated current collector electrode sheet are subjected to pressure fusion welding to ensure that each layer of the composite current collector electrode sheet is in full contact with the transfer foil to achieve the purpose of current conduction, complete welding, and obtain the laminated current collector electrode sheet.
[0007] Furthermore, the composite current collector is any one of a composite copper current collector or a composite aluminum current collector.
[0008] Furthermore, the electrode paste is prepared by mixing lithium iron phosphate material, conductive carbon black and polyvinylidene fluoride in a mass ratio of 95.6:2.1:2.3, and adding appropriate amounts of N-methylpyrrolidone thereto in batches, and stirring and mixing.
[0009] Furthermore, the specific method of welding in (2) is: welding a layer of transition foil on both sides of the blank area of the tab of the composite current collector electrode placed in the first layer from bottom to top of the stacked battery, as follows: Figure 1 As shown; the composite current collector electrode in other positions is welded with a layer of transfer foil on one side of the blank area of the pole ear, as shown in FIG. Figure 2 shown.
[0010] Furthermore, the specific method of welding in (3) is: welding the transition foil of the blank area of the tab of the composite current collector electrode in the lower layer to the blank area of the tab of the composite current collector electrode in the upper layer, as follows: Figure 3 shown.
[0011] Furthermore, the welding in (2) and (3) is performed by an ultrasonic welding machine, and its working parameters are: the mode is energy mode, the welding energy is 20~40J, the welding amplitude is 20~50μm, and the welding pressure is 10~40psi.
[0012] Furthermore, the specific position of the welding part in (4) is Figure 3 At the dotted line position.
[0013] Furthermore, the parameters of the pressure fusion welding process are: welding pressure is 80~100N, welding current is 25~130A, and welding time is 1~2s.
[0014] Furthermore, if the composite current collector is a composite copper current collector, the transfer foil is copper foil; if the composite current collector is a composite aluminum current collector, the transfer foil is aluminum foil.
[0015] Furthermore, in order to promote welding and improve welding strength, in the above (2) and (3), before welding, the blank area of the tab of the composite current collector electrode is coated with flux.
[0016] Furthermore, the soldering flux is obtained by mixing the following components: by mass percentage, rosin 1-5%, modified rosin 0.5-2%, activator 0.2-1.5%, surfactant 0.2-4%, antioxidant 0.5-1%, film former 0.1-1%, and solvent 86-93%.
[0017] Furthermore, the preparation method of the modified rosin is as follows: (1) under nitrogen protection, rosin amine and N,N'-carbonyldiimidazole are dissolved in dimethyl sulfoxide, stirred and heated to 65-85°C for reaction for 1-5 hours, and the reaction is terminated to obtain reaction liquid A; (2) the container containing the reaction liquid A is evacuated to a vacuum degree of 0.08-0.1 MPa; then the reaction liquid A is heated to 100-110°C, ethylene oxide is added, and then the reaction liquid A is continuously stirred and heated to 150-160°C for reaction for a period of time until the pressure in the container no longer changes, and finally the temperature is reduced to 100-110°C to obtain reaction liquid B; (3) potassium hydroxide and ethylene oxide are added to the reaction liquid B, Then, the mixture is stirred and heated to 150-160°C for a period of time until the pressure in the container no longer changes. The reaction is terminated. After the reaction system is naturally cooled to room temperature, deionized water is added, and the lower organic phase is collected after extraction. The organic phase is washed with brine for 1-5 times, and then dried with anhydrous sodium sulfate to obtain product A. (4) Product A and 5-carboxybenzotriazole are dissolved in dimethyl sulfoxide, stirred and heated to 65-85°C for 12-36 hours. The reaction is terminated. After the reaction system is naturally cooled to room temperature, dimethyl sulfoxide is removed by vacuum distillation, and then the organic phase is washed with brine for 1-5 times. Finally, the organic phase is dried with anhydrous sodium sulfate to obtain modified rosin.
[0018] Furthermore, the components required for preparing the product A are: by weight, 10-14 parts of rosin amine, 6-8 parts of N,N'-carbonyldiimidazole, 40 parts of dimethyl sulfoxide, 16-22 parts of ethylene oxide, and 0.01-0.03 parts of potassium hydroxide.
[0019] Furthermore, the components required for preparing the modified rosin are: by weight, 16 to 20 parts of product A, 10 to 14 parts of 5-carboxybenzotriazole, and 50 parts of dimethyl sulfoxide.
[0020] Furthermore, the active agent is an organic acid.
[0021] Furthermore, the organic acid includes but is not limited to a combination of one or more of succinic acid, adipic acid, azelaic acid, glutaric acid, citric acid, malic acid, tartaric acid, and salicylic acid.
[0022] Furthermore, the surfactant includes but is not limited to any one of nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, dodecylphenol polyoxyethylene ether, and fatty alcohol polyoxyethylene ether.
[0023] Furthermore, the antioxidant includes but is not limited to any one of benzotriazole, hydroquinone, and butylated hydroxytoluene.
[0024] Furthermore, the film-forming agent is a silicone-modified polyurethane, and its preparation method is: adding terminal hydroxyl silicone oil and acetone to the terminal isocyanate polyurethane prepolymer, stirring and heating to 70-85°C for reaction for 1-6 hours, terminating the reaction, allowing it to cool naturally to room temperature, and separating and purifying to obtain the silicone-modified polyurethane.
[0025] Furthermore, the mass ratio of the terminal hydroxyl silicone oil to the terminal isocyanate polyurethane prepolymer is (0.2-0.3):1.
[0026] Furthermore, the mass percentage of isocyanate groups in the isocyanate-terminated prepolymer is 24-28%; it was purchased from Shandong Jiaying Chemical Technology Co., Ltd.
[0027] Furthermore, the solvent includes but is not limited to any one of ethanol, ethylene glycol, propylene glycol, glycerol, and isopropanol.
[0028] In order to reduce the difficulty of welding and improve the welding fastness, the present invention is designed to use flux during the welding process. Considering that it is not easy to clean the stack after welding, if the traditional flux is used, some flux will inevitably remain in the welding part, and the residual flux will corrode the pole piece over time, thereby affecting the welding reliability, and more seriously causing short circuits, causing personal safety hazards. In addition, in order to improve the activity of the flux, some organic acid activators have to be added to the flux, and the organic acid activators are too corrosive, and after the oxide layer is cleared, it is very easy to cause damage to the current collector.
[0029] Therefore, in the present invention, the amino group of rosin amine is reacted with the imidazole group of N,N'-carbonyldiimidazole, and then polyoxyethylene ether is grafted on the product of the two, and finally it is reacted with the carboxyl group on 4-carboxybenzotriazole to prepare modified rosin; then it is mixed with rosin, active agent, surfactant, antioxidant, film-forming agent, solvent and other components to prepare a no-cleaning soldering flux. After welding, the no-cleaning soldering flux does not need to be cleaned and does not cause obvious damage to the electrode. Since the modified rosin contains polyoxyethylene ether chain ends and benzotriazole structures, it can play a corrosion inhibition role, thereby greatly weakening the influence of the active agent on the current collector. In addition, the polyoxyethylene ether chain ends on the modified rosin can also cooperate with surfactants to reduce the surface tension of the soldering flux, enhance the wetting power of the soldering flux, and then enhance the welding ability and improve the welding quality of the welding part; the benzotriazole structure can also cooperate with antioxidants to play an antioxidant role.
[0030] In order to further promote the dispersion of the active agent and enhance the effect of the flux, the invention further reacts terminal hydroxyl silicone oil and terminal isocyanate polyurethane prepolymer to prepare silicone-modified polyurethane; the silicone-modified polyurethane can cooperate with modified rosin and surfactant to promote the welding ability of the flux and improve the welding quality of the welding part; in addition, the silicone-modified polyurethane contains silicone oil chains, which can promote thermal conductivity, make the welding part evenly heated, reduce the generation of bubbles at the welding part, further enhance the welding ability, and improve the welding quality of the welding part.
[0031] Compared with the prior art, the present invention has the following beneficial effects: 1. The welding method (ultrasonic welding, pressure fusion welding) of the present invention can use less transfer foil and reduce the burden of subsequent pre-welding process; 2. The welding method of the present invention can greatly reduce the void rate of the welding part and improve the welding quality; 3. The flux in the present invention is a no-clean type flux, which avoids the tedious process of cleaning the current collector and does not cause corrosion to the electrode, greatly improving the welding reliability; under the synergistic effect of the welding method combined with the flux, the quality of the welding part can be greatly improved and the void rate of the welding part can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of welding on both sides of the blank area of the tab of the composite current collector at the first layer of the laminated current collector pole piece; Figure 2 A schematic diagram of single-side welding of the blank area of the tab of the composite current collector at the rest of the laminated current collector pole piece; Figure 3 Schematic diagram of the lamination of composite current collector pole pieces; Attached Figure 2 Middle: 1 is the transfer foil; 2 is the electrode paste; 3 is the blank area of the ear. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be noted that the purchasers of all raw materials involved in the present invention include, without any special restrictions, illustratively: Rosin with a purity of 99%, rosin amine with a purity of 99%, N,N'-carbonyldiimidazole with a purity of 99%, dimethyl sulfoxide with a purity of 99%, ethylene oxide with a purity of 99%, potassium hydroxide with a purity of 99%, 5-carboxybenzotriazole with a purity of 99%, CAS No. 23814-12-2, benzotriazole with a purity of 99%, and isopropanol with a purity of 99%, were all purchased from Hubei Yongkuo Technology Co., Ltd.; The purity of nonylphenol polyoxyethylene ether is 99%, item number: TX-10, purchased from Guangzhou Shuangmen Chemical Co., Ltd.; The molecular weight of the hydroxyl-terminated silicone oil was 1000 and it was purchased from Shanghai Tangui New Material Technology Co., Ltd.; The mass percentage of isocyanate groups in the isocyanate-terminated prepolymer was 24-28%, and it was purchased from Shandong Jiaying Chemical Technology Co., Ltd.
[0035] Embodiment 1: A method for welding a composite current collector electrode of a laminated battery: 1. Preparation of flux: 1. Preparation of modified rosin: (1) Under nitrogen protection, dissolve 12 parts of rosin amine and 7 parts of N,N'-carbonyldiimidazole in 40 parts of dimethyl sulfoxide, stir and heat to 75°C for reaction for 3 hours, terminate the reaction, and obtain reaction solution A; (2) evacuate the container containing reaction solution A to a vacuum degree of 0.08 MPa; then heat the reaction solution A to 105°C, add 3 parts of ethylene oxide, and continue to stir and heat to 155°C for a period of time until the pressure in the container no longer changes, and finally cool to 105°C to obtain reaction solution B; (3) add 0.02 parts of potassium hydroxide and 15 parts of ethylene oxide to reaction solution B, and then stir The mixture was heated to 155°C and reacted for a period of time until the pressure in the container no longer changed. The reaction was terminated. After the reaction system was naturally cooled to room temperature, 100 parts of deionized water was added. After extraction, the lower organic phase was collected, washed with brine for 5 times, and then dried with anhydrous sodium sulfate to obtain product A. (4) 18 parts of product A and 12 parts of 5-carboxybenzotriazole were dissolved in 50 parts of dimethyl sulfoxide, stirred and heated to 75°C for reaction for 24 hours. The reaction was terminated. After the reaction system was naturally cooled to room temperature, dimethyl sulfoxide was removed by vacuum distillation, and then washed with brine for 5 times. Finally, it was dried with anhydrous sodium sulfate to obtain modified rosin. 2. Preparation of organosilicon-modified polyurethane: Add 2.5 parts of terminal hydroxyl silicone oil and 20 parts of acetone to 10 parts of terminal isocyanate polyurethane prepolymer, stir and heat to 80°C for reaction for 5 hours, terminate the reaction, wait for it to cool naturally to room temperature, separate and purify, and obtain organosilicon-modified polyurethane; 3. Preparation of flux: According to the mass percentage, rosin 4%, modified rosin 1.5%, succinic acid 1%, nonylphenol polyoxyethylene ether 2.5%, benzotriazole 0.6%, silicone modified polyurethane 0.8%, isopropyl alcohol 89.6% are mixed to obtain the flux; 2. Welding: (1) The electrode paste is evenly coated on both surfaces of four composite copper current collectors (PET double-sided composite copper foil, with a total thickness of 7 μm, of which the PET layer thickness is 4 μm), leaving a blank area for the tabs, and dried to obtain composite copper current collector electrodes; (2) Evenly apply flux to the blank area of the tab of the composite copper collector electrode, then place it in a vacuum dryer and dry it at 90°C for 3 hours to complete the flux coating; (3) Using an ultrasonic welding machine (the working parameters of the ultrasonic welding machine are: energy mode, welding energy of 30J, welding amplitude of 35μm, welding pressure of 35psi), a 20μm thick copper foil is welded to the blank area of the tab of the composite copper collector electrode; wherein, a layer of copper foil is welded on both sides of the blank area of the tab of the composite copper collector placed in the first layer from bottom to top of the laminated battery, such as Figure 1 As shown, a layer of copper foil is welded on one side of the blank area of the tab at the rest of the composite copper current collectors. Figure 2 As shown; (4) stacking the composite copper current collectors welded in (3) in sequence. After the stacking is completed, an ultrasonic welding machine is used to weld the composite copper current collectors of the upper and lower stacks with the same parameters, so that the copper foil is in full contact with the blank areas of the tabs of the upper and lower composite current collector pole pieces, thereby obtaining a semi-finished laminated current collector pole piece; (5) The laminated current collector electrode semi-finished product is subjected to pressure fusion welding (pressure fusion welding parameters are: welding pressure is 90N, welding current is 50A, welding time is 1s) to make each layer of composite copper current collector and copper foil fully contact to achieve the purpose of current conduction, complete welding, and obtain the laminated current collector electrode.
[0036] Based on Example 1, Examples 2 to 3 and Comparative Examples 1 to 6 are provided, as follows: Example 2: Example 2 is based on Example 1, and the following adjustments are made: the amount of flux component used, and other processes remain unchanged, specifically: Preparation of soldering flux: According to mass percentage, rosin 4%, modified rosin 0.5%, succinic acid 1%, nonylphenol polyoxyethylene ether 2.5%, benzotriazole 0.6%, silicone modified polyurethane 0.1%, and isopropyl alcohol 91.3% are mixed to obtain the soldering flux.
[0037] Example 3: Example 3 is based on Example 1, and the amount of the flux component is adjusted, and other processes remain unchanged, specifically: Preparation of soldering flux: According to mass percentage, rosin 4%, modified rosin 2%, succinic acid 1%, nonylphenol polyoxyethylene ether 2.5%, benzotriazole 0.6%, silicone modified polyurethane 1%, and isopropyl alcohol 88.9% are mixed to obtain the soldering flux.
[0038] Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: no modified rosin is added, and other processes remain unchanged, specifically: Preparation of soldering flux: According to mass percentage, 5.5% of rosin, 1% of succinic acid, 2.5% of nonylphenol polyoxyethylene ether, 0.6% of benzotriazole, 0.8% of silicone-modified polyurethane, and 89.6% of isopropyl alcohol are mixed to obtain the soldering flux.
[0039] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustments: no silicone-modified polyurethane is added, and other processes remain unchanged, specifically: Preparation of soldering flux: According to mass percentage, rosin 4%, modified rosin 1.5%, succinic acid 1%, nonylphenol polyoxyethylene ether 2.5%, benzotriazole 0.6%, and isopropyl alcohol 90.4% are mixed to obtain the soldering flux.
[0040] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following adjustments: modified rosin and silicone-modified polyurethane are not added, and other processes remain unchanged, specifically: Preparation of soldering flux: According to mass percentage, 5.5% of rosin, 1% of succinic acid, 2.5% of nonylphenol polyoxyethylene ether, 0.6% of benzotriazole, and 90.4% of isopropyl alcohol are mixed to obtain the soldering flux.
[0041] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustments: no flux is applied to the blank area of the tab of the composite copper current collector, and other processes remain unchanged, specifically: welding: (1) The electrode paste is evenly coated on both surfaces of four composite copper current collectors (PET double-sided composite copper foil, with a total thickness of 7 μm, of which the PET layer thickness is 4 μm), leaving a blank area for the tabs, and dried to obtain composite copper current collector electrodes; (2) Using an ultrasonic welding machine (the working parameters of the ultrasonic welding machine are: energy mode, welding energy of 30J, welding amplitude of 35μm, welding pressure of 35psi), a 20μm thick copper foil is welded to the blank area of the coated tab; wherein, a layer of copper foil is welded on both sides of the blank area of the tab of the composite copper current collector placed in the first layer from bottom to top of the stacked battery, and a layer of copper foil is welded on one side of the blank area of the tab of the composite copper current collector in the remaining positions; (3) stacking the composite copper current collectors welded in (2) in sequence. After the stacking is completed, an ultrasonic welding machine is used to weld the composite copper current collectors of the upper and lower stacks with the same parameters, so that the copper foil is in full contact with the blank areas of the tabs of the upper and lower composite current collector pole pieces, thereby obtaining a semi-finished laminated current collector pole piece; (4) The laminated current collector electrode semi-finished product is subjected to pressure fusion welding (pressure fusion welding parameters are: welding pressure is 90N, welding current is 50A, welding time is 1s) to make each layer of composite copper current collector and copper foil fully contact to achieve the purpose of current conduction, complete welding, and obtain the laminated current collector electrode.
[0042] Comparative Example 5: Comparative Example 5 is based on Example 1, with the following adjustments: the laminated current collector electrode semi-finished product is not subjected to pressure welding, and other processes remain unchanged, specifically: welding: (1) The electrode paste is evenly coated on both surfaces of four composite copper current collectors (PET double-sided composite copper foil, with a total thickness of 7 μm, of which the PET layer thickness is 4 μm), leaving a blank area for the tabs, and dried to obtain composite copper current collector electrodes; (2) The flux is evenly coated on the blank area of the tab of the composite copper current collector, and then placed in a vacuum dryer and dried at 90°C for 3 hours to complete the flux coating; (3) Using an ultrasonic welding machine (the working parameters of the ultrasonic welding machine are: energy mode, welding energy of 30J, welding amplitude of 35μm, welding pressure of 35psi), a 20μm thick copper foil is welded to the blank area of the coated tab; wherein, a layer of copper foil is welded on both sides of the blank area of the tab of the composite copper current collector placed in the first layer from bottom to top of the stacked battery, and a layer of copper foil is welded on one side of the blank area of the tab of the composite copper current collector in the remaining positions; (4) The composite copper current collectors welded in (3) are stacked in sequence. After the stacking is completed, an ultrasonic welding machine is used to weld the composite copper current collectors of the upper and lower stacks with the same parameters so that the copper foil is in full contact with the blank areas of the tabs of the upper and lower composite current collector poles. The welding is completed to obtain a stacked current collector pole.
[0043] Comparative Example 6: Comparative Example 6 is based on Example 1, with the following adjustments: no flux is applied to the blank area of the tab of the composite copper current collector, and no pressure welding treatment is performed, and other processes remain unchanged, specifically: welding: (1) The electrode paste is evenly coated on both surfaces of four composite copper current collectors (PET double-sided composite copper foil, with a total thickness of 7 μm, of which the PET layer thickness is 4 μm), leaving a blank area for the tabs, and dried to obtain composite copper current collector electrodes; (2) Using an ultrasonic welding machine (the working parameters of the ultrasonic welding machine are: energy mode, welding energy of 30J, welding amplitude of 35μm, welding pressure of 35psi), a 20μm thick copper foil is welded to the blank area of the coated tab; wherein, a layer of copper foil is welded on both sides of the blank area of the tab of the composite copper current collector placed in the first layer from bottom to top of the stacked battery, and a layer of copper foil is welded on one side of the blank area of the tab of the composite copper current collector in the remaining positions; (3) The composite copper current collectors welded in (2) are stacked in sequence. After the stacking is completed, an ultrasonic welding machine is used to weld the composite copper current collectors of the upper and lower stacks with the same parameters so that the copper foil is in full contact with the blank areas of the tabs of the upper and lower composite current collector poles. The welding is completed to obtain a stacked current collector pole.
[0044] Performance test: The void ratio test was performed on the laminated current collector pole pieces obtained in Examples 1 to 3 and Comparative Examples 1 to 6, as described below: 1. Void rate test: The welding parts of the laminated current collector pole pieces are scanned using an ultrasonic scanning microscope, and the void rate of the welding parts is calculated to characterize the welding quality of the welding method of the present invention.
[0045] The test results of the above test contents are shown in Table 1 below: Table 1
[0046] Analysis of results: From the data in Table 1 above, it can be seen that the laminated current collector pole piece welded by the welding method of the present invention has excellent quality and a very small void rate, with the lowest reaching 2.2%, which is Example 1; in addition, by comparing the embodiments and comparative examples 1 to 6, it can be seen that: in the present invention, both the preparation of the flux and the welding process are crucial to the quality of the laminated current collector pole piece; in particular, when the two technologies are combined and act synergistically on the laminated current collector pole piece, the best result can be obtained.
[0047] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for welding a composite current collector electrode of a laminated battery, characterized in that: The specific method is: (1) coating the electrode paste on the surface of a plurality of composite current collectors, leaving a blank area for the electrode tab, to obtain a composite current collector electrode; (2) Welding the transfer foil in the blank area of the tab of the composite current collector electrode to be laminated; (3) stacking the composite current collector pole pieces welded in (2) in sequence, and after the stacking is completed, welding the upper and lower stacked composite current collector pole pieces to obtain a semi-finished laminated current collector pole piece; (4) The welding parts on the semi-finished laminated current collector electrode sheet are subjected to pressure fusion welding to complete the welding and obtain the laminated current collector electrode sheet.
2. The method for welding a composite current collector electrode of a laminated battery according to claim 1, characterized in that: The specific welding method in (2) is as follows: a layer of transition foil is welded on both sides of the blank area of the tab of the composite current collector electrode sheet placed in the first layer from bottom to top of the stacked battery; a layer of transition foil is welded on one side of the blank area of the tab of the composite current collector electrode sheet in the remaining positions; the specific welding method in (3) is as follows: the transition foil of the blank area of the tab of the composite current collector electrode sheet in the lower layer is welded together with the blank area of the tab of the composite current collector electrode sheet in the upper layer.
3. The method for welding composite current collector pole pieces of a laminated battery according to claim 1 is characterized in that: The welding in (2) and (3) is carried out by an ultrasonic welding machine, and its working parameters are: the mode is energy mode, the welding energy is 20~40J, the welding amplitude is 20~50μm, and the welding pressure is 10~40psi; the parameters of the pressure fusion welding process in (3) are: welding pressure is 80~100N, welding current is 25~130A, and welding time is 1~2s.
4. The method for welding composite current collector pole pieces of a laminated battery according to claim 1, characterized in that: The composite current collector is any one of a composite copper current collector and a composite aluminum current collector; if the composite current collector is a composite copper current collector, the transition foil is copper foil; if the composite current collector is a composite aluminum current collector, the transition foil is aluminum foil.
5. The method for welding composite current collector pole pieces of a laminated battery according to claim 1, characterized in that: The electrode paste is prepared by mixing lithium iron phosphate material, conductive carbon black and polyvinylidene fluoride in a mass ratio of 95.6:2.1:2.3, and adding appropriate amount of N-methylpyrrolidone thereto in batches, stirring and mixing.
6. The method for welding composite current collector pole pieces of a laminated battery according to claim 1, characterized in that: In the above (2) and (3), before welding, the blank area of the tab of the composite current collector electrode is coated with flux.
7. The method for welding composite current collector pole pieces of a laminated battery according to claim 6, characterized in that: The soldering flux is obtained by mixing the following components: calculated by mass percentage, rosin 1-5%, modified rosin 0.5-2%, activator 0.2-1.5%, surfactant 0.2-4%, antioxidant 0.5-1%, film former 0.1-1%, and solvent 86-93%.
8. The method for welding composite current collector pole pieces of a laminated battery according to claim 7, characterized in that: The preparation method of the modified rosin is as follows: (1) under nitrogen protection, rosin amine and N,N'-carbonyldiimidazole are dissolved in dimethyl sulfoxide, and the mixture is stirred and heated to 65-85°C for reaction for 1-5 hours, and the reaction is terminated to obtain a reaction liquid A; (2) a container containing the reaction liquid A is evacuated to a vacuum degree of 0.08-0.1 MPa; then the reaction liquid A is heated to 100-110°C, ethylene oxide is added, and then the mixture is stirred and heated to 150-160°C for reaction for a period of time until the pressure in the container is reduced to 0.1 MPa. The pressure no longer changes, and finally the temperature is lowered to 100-110°C to obtain reaction solution B; (3) potassium hydroxide and ethylene oxide are added to reaction solution B, and then stirred and heated to 150-160°C for a period of time until the pressure in the container no longer changes, the reaction is terminated, and product A is obtained after separation and purification; (4) product A and 5-carboxybenzotriazole are dissolved in dimethyl sulfoxide, stirred and heated to 65-85°C for 12-36 hours, the reaction is terminated, and modified rosin is obtained after separation and purification; The components required for the preparation of the product A are: by weight, 10-14 parts of rosin amine, 6-8 parts of N,N'-carbonyldiimidazole, 40 parts of dimethyl sulfoxide, 16-22 parts of ethylene oxide, and 0.01-0.03 parts of potassium hydroxide; The components required for preparing the modified rosin are: by weight, 16-20 parts of product A, 10-14 parts of 5-carboxybenzotriazole, and 50 parts of dimethyl sulfoxide.
9. The method for welding composite current collector pole pieces of a laminated battery according to claim 7, characterized in that: The active agent is an organic acid; the surfactant includes any one of nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, dodecylphenol polyoxyethylene ether, and fatty alcohol polyoxyethylene ether; the antioxidant includes any one of benzotriazole, hydroquinone, and butylated hydroxytoluene; the solvent includes any one of ethanol, ethylene glycol, propylene glycol, glycerol, and isopropanol.
10. The method for welding composite current collector pole pieces of a laminated battery according to claim 7, characterized in that: The film-forming agent is silicone-modified polyurethane, and its preparation method is as follows: adding terminal hydroxyl silicone oil and acetone to terminal isocyanate polyurethane prepolymer, stirring and heating to 70-85°C for reaction for 1-6 hours, ending the reaction, waiting for it to cool naturally to room temperature, and separating and purifying to obtain silicone-modified polyurethane; The mass ratio of the terminal hydroxyl silicone oil to the terminal isocyanate polyurethane prepolymer is (0.2-0.3):1; the mass percentage of isocyanate groups in the terminal isocyanate prepolymer is 24-28%.
Citation Information
Patent Citations
Method for preparing ethoxyabietic amine by spraying process
CN101121783A
Halogen-free tin-bismuth-copper soldering paste and preparation method thereof
CN101695794A
Halogen-free high-impedance soldering flux and preparation method
CN102554518A
Soldering flux
CN102909493A
Low-temperature, halogen-free, low-solid-content modified rosin-type welding flux and preparation method thereof
CN108817731A